Lithium ion battery binder for inhibiting silicon expansion, negative pole piece, lithium ion battery and electric device

By using dynamic reversible covalent cross-linked polymer networks and multiple dynamic cross-linked networks, the performance degradation problem of lithium-ion batteries caused by silicon expansion was solved, achieving battery stability and efficient energy storage.

CN121379425APending Publication Date: 2026-01-23JIANGSU RELIANCE ENERGY TECHNOLOGY CO LTD
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202511520578.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-10-23
Publication Date
2026-01-23

AI Technical Summary

Technical Problem

In lithium-ion batteries, the capacity of silicon anodes decreases due to volume expansion, and the SEI film thickens continuously, affecting battery performance.

Method used

A cross-linked polymer network with dynamic reversible covalent bonds is used, which combines hydrogen bonds and metal coordination bonds into a multi-dynamic cross-linked network to buffer the volume expansion stress of silicon particles. Energy is consumed through reversible bond breaking and recombination, thus stabilizing the electrode structure.

Benefits of technology

It effectively suppresses silicon expansion, maintains the mechanical strength and electrochemical performance of the battery, and improves the cycle stability and rate performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_4
    Figure SMS_4
  • Figure SMS_11
    Figure SMS_11
Patent Text Reader

Abstract

The invention provides a lithium ion battery binder for inhibiting silicon expansion, a negative pole piece, a lithium ion battery and an electric device, and relates to the technical field of lithium ion batteries. The lithium ion battery binder capable of inhibiting silicon expansion comprises a first polymer and a second polymer, wherein the first polymer is a cross-linked polymer with dynamic reversible covalent bonds; wherein the dynamic reversible covalent bond comprises a disulfide bond or a borate bond; the binder network provided by the invention not only can effectively limit the excessive slippage of a polymer and provide higher mechanical strength, but also can generate reversible fracture and recombination at a stress concentration point in the charging and discharging process due to the dynamic reversibility of a disulfide bond or a borate bond, converts concentrated stress into fracture energy of a chemical bond and dissipates the fracture energy, so that the mechanical strength of the polymer is improved, and the service life of the polymer is prolonged. Therefore, permanent damage of the network is avoided, the pole piece structure is kept complete in long-term circulation, and stable electrochemical performance is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the technical field of lithium-ion batteries, and in particular to a lithium-ion battery binder for inhibiting silicon expansion, a negative electrode sheet, a lithium-ion battery, and an electrical device. Background Technology

[0002] Lithium-ion batteries are widely used in consumer electronics, energy storage, and electric vehicles due to their high energy density and good cycle performance. Traditional graphite anode materials are increasingly unable to meet the demands for high energy density due to capacity limitations (theoretical capacity of only 372 mAh / g). Elemental silicon (Si), with its high theoretical capacity (4200 mAh / g), low lithium intercalation potential, abundant resources, and environmental friendliness, is considered an ideal anode material for next-generation lithium-ion batteries.

[0003] However, silicon expands during charging; that is, the silicon anode undergoes a huge volume change during charging and discharging. During this process, silicon particles experience a violent cycle of expansion and contraction. This repeated stress can cause the silicon particles to crack and pulverize, and the active material to detach from the electrode, resulting in a permanent and rapid capacity decay of the battery. Furthermore, during the first charge, the electrolyte decomposes on the surface of the anode, forming a thin, stable protective film called the SEI film. For graphite, this film is relatively stable once formed. But for silicon, the huge volume changes continuously rupture and tear the existing SEI film. The exposed fresh silicon surface reacts with the electrolyte, continuously generating a new SEI film; this continuous consumption of lithium ions and electrolyte leads to a sustained decrease in battery capacity, and the SEI film thickens, increasing internal resistance and affecting the battery's rate performance.

[0004] In view of this, the present invention is hereby proposed. Summary of the Invention

[0005] The present invention aims to provide a lithium-ion battery binder for suppressing silicon expansion, a negative electrode sheet, a lithium-ion battery, and an electrical device. The lithium-ion battery binder for suppressing silicon expansion comprises a cross-linked polymer network with dynamically reversible covalent bonds, which buffers the volume expansion stress of silicon particles during charging and discharging through reversible bond breakage and recombination.

[0006] In order to achieve the above-mentioned objectives of the present invention, the following technical solution is adopted: In a first aspect, the present invention provides a lithium-ion battery binder for suppressing silicon expansion, comprising: a first polymer, wherein the crosslinked polymer having dynamically reversible covalent bonds has the following structural formula I:

[0007] Formula I Where R is selected from or R1 and R2 are each independently selected from hydrogen or substituted or unsubstituted C1~C6 straight-chain or branched alkyl groups, and R3 is selected from hydrogen, substituted or unsubstituted C1~C6 straight-chain or branched alkyl groups, or substituted or unsubstituted C6~C12 aryl groups; m is 1~1000 and n is 1~1000.

[0008] Furthermore, R1 and R2 are each independently selected from C1-C4 straight-chain or branched alkyl groups.

[0009] Furthermore, R3 is selected from phenyl.

[0010] Furthermore, the lithium-ion battery binder for inhibiting silicon expansion also includes a second polymer, and the second polymer includes functional groups for forming hydrogen bonds with the first polymer; wherein the functional groups for forming hydrogen bonds with the first polymer include any one or a combination of at least two of hydroxyl, amide, amino, or carboxyl groups.

[0011] Furthermore, the mass ratio of the first polymer to the second polymer is 1:(0.1~10).

[0012] Furthermore, the second polymer comprises polyvinyl alcohol and / or polyacrylamide.

[0013] Furthermore, the weight-average molecular weight of the polyvinyl alcohol is 80,000 to 120,000.

[0014] Furthermore, the weight-average molecular weight of the polyacrylamide is 4,000,000 to 6,000,000.

[0015] Furthermore, the lithium-ion battery binder for inhibiting silicon expansion also includes a third compound, which comprises metal ions for forming metal coordination bonds with the first polymer; wherein the metal ions include Fe. 3+ Al 3+ Zn 2+ or Ca 2+ Any one or at least two of them.

[0016] Furthermore, the third compound includes any one or a combination of at least two of chloride, acetate, sulfate, nitrate, acetate, or oxalate.

[0017] Furthermore, the molar ratio of the first polymer to the third compound is 1:(0.01~0.5).

[0018] In a second aspect, the present invention provides a method for preparing a lithium-ion battery binder for inhibiting silicon expansion as described in the first aspect, the method comprising: Polyacrylic acid and a compound with dynamic reversible covalent bonds undergo a condensation reaction in a solvent to obtain the lithium-ion battery binder that inhibits silicon expansion.

[0019] Furthermore, when the lithium-ion battery binder for inhibiting silicon expansion further includes a second polymer, the preparation method includes: Polyacrylic acid, a second polymer, and a compound with dynamic reversible covalent bonds undergo a condensation reaction in a solvent to obtain the lithium-ion battery binder that inhibits silicon expansion.

[0020] Furthermore, when the lithium-ion battery binder for inhibiting silicon expansion further includes a third compound, the preparation method includes: Polyacrylic acid and a compound with dynamic reversible covalent bonds undergo a condensation reaction in a solvent to obtain a reaction solution containing a first polymer; the reaction solution containing the first polymer then undergoes a coordination reaction with a third compound to obtain the lithium-ion battery binder that inhibits silicon expansion.

[0021] Furthermore, when the lithium-ion battery binder for inhibiting silicon expansion further includes a second polymer and a third compound, the preparation method includes: Polyacrylic acid, a second polymer, and a compound with dynamic reversible covalent bonds undergo a condensation reaction in a solvent to obtain a polymer mixture reaction solution; the polymer mixture reaction solution then undergoes a coordination reaction with a third compound to obtain the lithium-ion battery binder that inhibits silicon expansion.

[0022] Furthermore, the condensation reaction is carried out at a temperature of 60-80°C for 3-4 hours.

[0023] Furthermore, the coordination reaction is carried out at a temperature of 20-30°C for 0.5-2 hours.

[0024] Thirdly, the present invention provides a negative electrode sheet, the negative electrode sheet comprising a current collector and a negative electrode active material coating disposed on at least one side of the current collector; wherein the negative electrode active material coating comprises a lithium-ion battery binder for inhibiting silicon expansion as described in the first aspect.

[0025] Furthermore, the content of the lithium-ion battery binder that inhibits silicon expansion accounts for 0.5 to 8% of the total mass of the negative electrode active material coating.

[0026] Furthermore, the negative electrode active material coating also includes graphite, silicon-based active material, and conductive agent.

[0027] Furthermore, the mass ratio of the graphite, silicon-based active material, conductive agent, and lithium-ion battery binder that inhibits silicon expansion is (70~95):(5~30):(1~10):(0.5~8).

[0028] Fourthly, the present invention provides a lithium-ion battery, the lithium-ion battery comprising the negative electrode sheet as described in the third aspect.

[0029] Furthermore, after 300 1C charge-discharge cycles, the capacity retention rate of the lithium-ion battery is >85%.

[0030] Furthermore, after three charge-discharge cycles, the peel strength between the negative electrode active material coating and the current collector is ≥60 N / m.

[0031] Furthermore, after 200 1C charge-discharge cycles, the thickness expansion rate of the negative electrode sheet is ≤8%.

[0032] Fifthly, the present invention provides an electrical device comprising a lithium-ion battery as described in the fourth aspect.

[0033] Compared with the prior art, the present invention has the following beneficial effects: (1) The binder of the present invention includes a first polymer. Since the polymer contains a cross-linked polymer network with dynamic reversible covalent bonds, that is, a three-dimensional network is formed by establishing dynamic covalent cross-linking points. This network can not only effectively limit the excessive slip of the polymer and provide higher mechanical strength, but also convert the concentrated stress into the breaking energy of the chemical bond and dissipate it through the reversible breaking and recombination of the bond during the charging and discharging process, thereby avoiding permanent damage to the network. At the same time, it buffers the volume expansion stress of silicon particles and achieves stable electrochemical performance.

[0034] (2) The adhesive of the present invention includes a second polymer, which introduces non-covalent dynamic crosslinking bonds (including hydrogen bonds) into the network of the adhesive, further forming a multi-layer dynamic crosslinking network; wherein, the hydrogen bond has the characteristics of moderate strength and extremely fast formation and breakage speed. As a primary energy dissipation unit, it can break / reassemble quickly under small deformation, consuming a large amount of energy, thereby protecting the reversible covalent bond network from frequent impacts.

[0035] (3) The binder of the present invention includes a third compound, which introduces non-covalent dynamic cross-linking bonds (metal coordination bonds) into the network of the binder, further forming a multi-layer dynamic cross-linking network; wherein, the metal ions form coordination bonds with carboxyl groups, which can significantly improve the modulus of the network, making the electrode more compact and better suppressing the initial expansion of silicon particles; and the coordination bonds also have dynamic properties, and can undergo bonding-dissociation under high stress, further enriching the pathways for energy dissipation. Detailed Implementation

[0036] Unless otherwise defined herein, the scientific and technical terms used in conjunction with this invention shall have the meanings commonly understood by one of ordinary skill in the art. The meaning and scope of terms shall be clear; however, in any case of potential ambiguity, the definitions provided herein shall prevail over any dictionary or foreign definitions. In this application, unless otherwise stated, the use of "or" means "and / or". Furthermore, the use of the term "comprising" and other forms is non-limiting.

[0037] The technical solution of the present invention will be clearly and completely described below with reference to the embodiments. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0038] The present invention will be further illustrated by the following examples. Unless otherwise specified, the materials in the examples are prepared according to existing methods or purchased directly from the market.

[0039] In a first aspect, the present invention provides a lithium-ion battery binder for suppressing silicon expansion, the lithium-ion battery binder for suppressing silicon expansion comprising: a first polymer, the crosslinked polymer having a dynamically reversible covalent bond having the structural formula shown in Formula I below:

[0040] Formula I.

[0041] As an optional implementation, R is selected from... or .

[0042] In this invention, the lithium-ion battery binder for inhibiting silicon expansion comprises: a first polymer, which is a cross-linked polymer with dynamically reversible covalent bonds; wherein the dynamically reversible covalent bonds include disulfide bonds or borate ester bonds; by establishing dynamically covalent cross-linking points between polyacrylic acid chains through compounds with dynamically reversible covalent bonds, a three-dimensional network is formed. This network not only effectively limits excessive polymer slippage and provides higher mechanical strength, but also, due to the "dynamic reversibility" of disulfide bonds or borate ester bonds—that at stress concentration points during the charge-discharge process, disulfide bonds undergo reversible breakage and recombination, converting the concentrated stress into the breaking energy of chemical bonds and dissipating it—thus avoiding permanent network damage. This allows the electrode structure to remain intact during long-term cycling, achieving stable electrochemical performance.

[0043] As an optional implementation, R1 and R2 are each independently selected from hydrogen or substituted or unsubstituted C1~C6 (e.g., C1, C2, C3, C4, C5, C6) straight-chain or branched alkyl groups.

[0044] As an optional implementation, R3 is selected from hydrogen, substituted or unsubstituted C1~C6 (e.g., C1, C2, C3, C4, C5, C6) straight-chain or branched alkyl, and substituted or unsubstituted C6~C12 (e.g., C6, C7, C8, C9, C10, C11, C12) aryl.

[0045] As an optional implementation, m is 1 to 1000, for example, it can be 1, 50, 100, 200, 300, 400, 500, 600, 700, 800, 900, 1000, etc.

[0046] As an optional implementation, n is 1 to 1000, for example, it can be 1, 50, 100, 200, 300, 400, 500, 600, 700, 800, 900, 1000, etc.

[0047] As an optional implementation, R1 and R2 are each independently selected from C1-C4 straight-chain or branched alkyl groups, such as methyl, ethyl, n-propyl, isopropyl, n-butyl, sec-butyl, isobutyl, and tert-butyl.

[0048] As an optional implementation, R3 is selected from phenyl.

[0049] As an optional embodiment, the lithium-ion battery binder for suppressing silicon expansion further includes a second polymer, and the second polymer includes functional groups for forming hydrogen bonds with the first polymer; wherein the functional groups for forming hydrogen bonds with the first polymer include any one or a combination of at least two of hydroxyl, amide, amino, or carboxyl groups.

[0050] In this invention, the introduction of a second polymer provides functional groups such as hydroxyl, amide, amino, or carboxyl groups for forming hydrogen bonds with the first polymer, resulting in a dense hydrogen bond network. These hydrogen bonds possess moderate strength and extremely rapid formation and breakage rates. As primary energy dissipation units, they can rapidly break / reassemble under minute deformations, consuming a large amount of energy, thereby protecting the dynamically reversible covalent bond network from frequent impacts. This manifests as a significant improvement in the adhesive's toughness and initial bonding strength.

[0051] As an optional implementation, the mass ratio of the first polymer to the second polymer is 1:(0.1~10), for example, it can be 1:0.1, 1:0.5, 1:1, 1:2, 1:3, 1:4, 1:5, 1:6, 1:7, 1:8, 1:9, 1:10, etc.

[0052] As an optional implementation, the second polymer includes polyvinyl alcohol (PVA) and / or polyacrylamide (PAM).

[0053] As an optional implementation, the weight-average molecular weight of the polyvinyl alcohol is 80,000 to 120,000, for example, it can be 80,000, 85,000, 90,000, 95,000, 100,000, 105,000, 110,000, 115,000, 120,000, etc.

[0054] As an optional implementation, the weight-average molecular weight of the polyacrylamide is 4,000,000 to 6,000,000, for example, 4,000,000, 4,500,000, 5,000,000, 5,500,000, 6,000,000, etc.

[0055] As an optional embodiment, the lithium-ion battery binder for suppressing silicon expansion further includes a third compound, the third compound comprising metal ions for forming metal coordination bonds with the first polymer; wherein the metal ions include Fe. 3+ Al 3+ Zn 2+ or Ca 2+ Any one or at least two of them.

[0056] In this invention, a third compound is introduced, which introduces Fe. 3+ Al 3+ Zn 2+ or Ca 2+ These metal ions form coordinate bonds with carboxyl groups. These coordinate bonds are stronger than hydrogen bonds, significantly increasing the modulus of the network, making the electrode more compact, and better suppressing the initial expansion of silicon particles. Simultaneously, the coordinate bonds also exhibit dynamic behavior, undergoing bonding-dissociation under high stress, further enriching the pathways for energy dissipation.

[0057] As an optional implementation, the third compound includes any one or a combination of at least two of chloride, acetate, sulfate, nitrate, acetate or oxalate.

[0058] As an optional implementation, the molar ratio of the first polymer to the third compound is 1:(0.01~0.5), for example, it can be 1:0.01, 1:0.05, 1:0.1, 1:0.2, 1:0.3, 1:0.4, 1:0.5, etc.

[0059] In a second aspect, the present invention provides a method for preparing a lithium-ion battery binder for inhibiting silicon expansion as described in the first aspect, the method comprising: Polyacrylic acid and a compound with dynamic reversible covalent bonds undergo a condensation reaction in a solvent to obtain the lithium-ion battery binder that inhibits silicon expansion.

[0060] As an optional implementation, when the lithium-ion battery binder for inhibiting silicon expansion further includes a second polymer, the preparation method includes: Polyacrylic acid, a second polymer, and a compound with dynamic reversible covalent bonds undergo a condensation reaction in a solvent to obtain the lithium-ion battery binder that inhibits silicon expansion.

[0061] As an optional implementation, when the lithium-ion battery binder for inhibiting silicon expansion further includes a third compound, the preparation method includes: Polyacrylic acid and a compound with dynamic reversible covalent bonds undergo a condensation reaction in a solvent to obtain a reaction solution containing a first polymer; the reaction solution containing the first polymer then undergoes a coordination reaction with a third compound to obtain the lithium-ion battery binder that inhibits silicon expansion.

[0062] As an optional implementation, when the lithium-ion battery binder for inhibiting silicon expansion further comprises a second polymer and a third compound, the preparation method includes: Polyacrylic acid, a second polymer, and a compound with dynamic reversible covalent bonds undergo a condensation reaction in a solvent to obtain a polymer mixture reaction solution; the polymer mixture reaction solution then undergoes a coordination reaction with a third compound to obtain the lithium-ion battery binder that inhibits silicon expansion.

[0063] As an optional implementation, the temperature of the condensation reaction is 60~80℃, for example, 60℃, 65℃, 70℃, 75℃, 80℃, etc., and the time of the condensation reaction is 3~4 h, for example, 3 h, 3.2 h, 3.4 h, 3.5 h, 3.6 h, 3.8 h, 4 h, etc.

[0064] As an optional implementation, when the compound having a dynamically reversible covalent bond is a compound having a disulfide bond, the condensation reaction is carried out in the presence of a condensing agent.

[0065] As an optional embodiment, the condensing agent is 1-ethyl-(3-dimethylaminopropyl)carbodiimide and / or 1-ethyl-(3-dimethylaminopropyl)carbodiimide salt.

[0066] As an optional implementation, when the compound having a dynamically reversible covalent bond is a compound having a boric acid bond, the condensation reaction is carried out in the presence of a weak acid.

[0067] As an optional implementation, the pH of the system in the presence of the weak acid is 4 to 6, for example, it can be 4, 4.5, 5, 5.5, 6, etc.

[0068] As an optional implementation, the weak acid is selected from acetic acid.

[0069] As an optional implementation, the temperature of the coordination reaction is 20~30℃, for example, 20℃, 22℃, 24℃, 25℃, 26℃, 28℃, 30℃, etc., and the time of the coordination reaction is 0.5~2 h, for example, 0.5 h, 1 h, 1.5 h, 2 h, etc.

[0070] As an optional implementation, the compound with dynamically reversible covalent bonds is a compound with disulfide bonds, and its structural formula is [insert structural formula here]. R1 and R2 are each independently selected from hydrogen or substituted or unsubstituted C1-C6 straight-chain or branched alkyl groups.

[0071] As an optional implementation, the compound with dynamically reversible covalent bonds is a compound with boric acid bonds, and its structural formula is as follows: R3 is selected from hydrogen, substituted or unsubstituted C1-C6 straight-chain or branched alkyl groups, and substituted or unsubstituted C6-C12 aryl groups.

[0072] Thirdly, the present invention provides a negative electrode sheet, the negative electrode sheet comprising a current collector and a negative electrode active material coating disposed on at least one side of the current collector; wherein the negative electrode active material coating comprises a lithium-ion battery binder for inhibiting silicon expansion as described in the first aspect.

[0073] As an optional implementation, the content of the lithium-ion battery binder that inhibits silicon expansion accounts for 0.5 to 8% of the total mass of the negative electrode active material coating, for example, it can be 0.5%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, etc.

[0074] As an optional implementation, the negative electrode active material coating may further include graphite, silicon-based active material, and conductive agent.

[0075] As an optional implementation, the silicon-based active material includes silicon carbon.

[0076] As an optional implementation, the conductive agent includes conductive agent SP.

[0077] As an optional implementation, the mass ratio of the graphite, silicon-based active material, conductive agent and the lithium-ion battery binder that inhibits silicon expansion is (70~95):(5~30):(1~10):(0.5~8); Among them, "70~95" can be, for example, 70, 80, 85, 90, 95, etc.; Among them, "5~30" can be, for example, 5, 10, 15, 20, 25, 30, etc.; Among them, "1~10" can be, for example, 1, 2, 4, 5, 6, 8, 10, etc.; Among them, "0.5~8" can be, for example, 0.4, 1, 2, 4, 5, 6, 8, etc.

[0078] As an optional implementation, the present invention provides a lithium-ion battery, the lithium-ion battery comprising a negative electrode as described in the third aspect.

[0079] As an optional implementation, after 300 1C charge-discharge cycles, the capacity retention rate of the lithium-ion battery is >85%, for example, it can be 86%, 88%, 90%, 92%, 94%, 95%, etc.

[0080] As an optional implementation, after the negative electrode sheet undergoes 3 charge-discharge cycles, the peel strength between the negative electrode active material coating and the current collector is ≥60 N / m, for example, it can be 60 N / m, 65 N / m, 70 N / m, 75 N / m, etc.

[0081] As an optional implementation, after 200 1C charge-discharge cycles, the thickness expansion rate of the negative electrode sheet is ≤8%, for example, it can be 8%, 7%, 6%, 5%, etc.

[0082] Fifthly, the present invention provides an electrical device comprising a lithium-ion battery as described in the fourth aspect.

[0083] The present invention will be further illustrated by the following examples. Unless otherwise specified, the materials in the examples are prepared according to existing methods or purchased directly from the market.

[0084] Example 1 This embodiment provides a lithium-ion battery binder for inhibiting silicon expansion, as well as a negative electrode active material coating containing the binder, a negative electrode sheet, and a lithium-ion battery; the preparation method of the lithium-ion battery includes the following steps: (1) Preparation of lithium-ion battery binder to suppress silicon expansion: 1.0 g of polyacrylic acid (PAA, Mw=450,000) was dissolved in 100 mL of deionized water; then, 0.6 g of dithiodipropionic acid and 0.8 g of 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride (EDC·HCl) as a condensing agent were added sequentially, and the mixture was stirred at 80 °C for 3 h. After the reaction was completed, the mixture was cooled to room temperature to obtain a dynamic crosslinking adhesive solution. The core reaction involves the condensation reaction of the carboxyl groups of polyacrylic acid (PAA) and dithiodipropionic acid under the catalysis of carbodiimide (EDC). EDC first activates one carboxyl group of dithiodipropionic acid, forming an activated O-acylisourea intermediate. This intermediate then undergoes nucleophilic substitution with the carboxyl group on the PAA molecular chain, removing one water molecule and forming ester crosslinking bridges connected by disulfide bonds, thereby linking the linear PAA molecular chains into a three-dimensional network structure. This crosslinking reaction proceeds stepwise, with one dithiodipropionic acid molecule capable of connecting two PAA segments. In the 1H NMR spectrum, a new characteristic peak belonging to the ester-peptide subproton (-COO-CH2-) appears at ~4.2 ppm, while in the infrared spectrum, a peak appears at ~1740 cm⁻¹. -1 The presence of characteristic absorption peaks of the ester carbonyl group (-C=O) at the position confirms that the ester cross-linked structure was generated by the reaction of the carboxyl group. The simplified overall reaction equation can be expressed as: PAA-COOH+HOOC-CH2-CH2-SS-CH2-CH2-COOH+HOOC-PAA PAA-CO-O-CH2-CH2-SS-CH2-CH2-CO-O-PAA+2H2O.

[0085] (2) Method for manufacturing negative electrode plates: Artificial graphite, silicon carbon material, conductive agent SP, and the dynamic crosslinking binder solution obtained in step (1) were mixed in a mass ratio of 80:11:5:4. Deionized water was then added and stirred to form a uniform and stable negative electrode slurry with a solid content of 40%. The negative electrode slurry was uniformly coated onto an 8 μm copper foil of the negative electrode current collector, and then dried and cold-pressed to obtain a negative electrode sheet with a compaction density of 1.6 g / cm³. 3 .

[0086] (3) Method for manufacturing positive electrode plates: Take positive electrode active material (LiNi) 0.8 Co 0.1 Mn 0.1 O2), conductive carbon black, carbon nanotubes, and polyvinylidene fluoride (PVDF) were thoroughly mixed in an N-methylpyrrolidone solvent system at a mass ratio of 96:1:1:2 to form a stable positive electrode slurry with a solid content of 70%. The positive electrode slurry was then uniformly coated onto a 12 μm aluminum foil as the positive electrode current collector. After drying and cold pressing, the positive electrode sheet was obtained with a compaction density of 3.4 g / cm³. 3 .

[0087] (4) Preparation of electrolyte: The electrolyte is prepared by mixing lithium hexafluorophosphate (LiPF6), ethylene carbonate (EC), dimethyl carbonate (DMC), fluoroethylene carbonate (FEC), ethylene sulfate (DTD), and vinylene carbonate (VC) in a mass percentage ratio of 10.0:20.0:55.0:2.0:8.0:5.0.

[0088] (5) Assembly of lithium-ion batteries: The positive and negative electrode sheets obtained in the above steps are rolled, slit, and then wound together with the separator to obtain a 21700 cylindrical battery core. The battery core is then welded to the connecting piece and installed into the battery casing. After completing the liquid injection, sealing, and formation processes, the lithium-ion battery of Example 1 is obtained. The casing of the lithium-ion battery is cylindrical with dimensions of 21.0 mm in diameter and 70.0 mm in length.

[0089] Example 2 This embodiment provides a lithium-ion battery binder for inhibiting silicon expansion, as well as a negative electrode active material coating, a negative electrode sheet, and a lithium-ion battery containing the binder; the only difference from Example 1 is that 0.6 g of dithiodipropionic acid in step (1) is replaced with 0.55 g of phenylboronic acid, and the reaction is carried out at 70°C for 4 h under weakly acidic conditions (acetic acid, pH=5.0), and all other aspects are the same as in Example 1. The core reaction between PAA and phenylboronic acid involves the formation of a borate ester bond between the carboxyl group of PAA and the borate group of phenylboronic acid under weakly acidic conditions. The simplified overall reaction equation is: PAA-COOH + C6H5B(OH)2 + HOOC-PAA PAA-CO-OB(C6H5)-O-CO-PAA+2H2O. Characteristic peaks of benzene ring protons (~7.5-8.0 ppm) can be observed in the 1H NMR spectrum, while the infrared spectrum shows peaks at ~1340 cm⁻¹. -1 The presence of BO stretching vibration absorption peaks nearby confirms the formation of the boronic ester cross-linked structure.

[0090] Example 3 This embodiment provides a lithium-ion battery binder for inhibiting silicon expansion, as well as a negative electrode active material coating, a negative electrode sheet, and a lithium-ion battery containing the binder; the only difference from Embodiment 1 is that the amount of crosslinking agent added in step (1) is 0.3 g dithiodipropionic acid, and all other aspects are the same as in Embodiment 1.

[0091] Example 4 This embodiment provides a lithium-ion battery binder for inhibiting silicon expansion, as well as a negative electrode active material coating, a negative electrode sheet, and a lithium-ion battery containing the binder; the only difference from Embodiment 1 is that the amount of crosslinking agent added in step (1) is 0.75 g of dithiodipropionic acid, and all other aspects are the same as in Embodiment 1.

[0092] Example 5 This embodiment provides a lithium-ion battery binder that inhibits silicon expansion, as well as a negative electrode active material coating, a negative electrode sheet, and a lithium-ion battery containing the binder. The only difference from Embodiment 1 is that in step (2), the mass ratio of artificial graphite, silicon carbon material, conductive agent SP, and the dynamic crosslinking binder solution obtained in step (1) in the negative electrode sheet is 80:11:8.2:0.8. All other aspects are the same as in Embodiment 1.

[0093] Example 6 This embodiment provides a lithium-ion battery binder that inhibits silicon expansion, as well as a negative electrode active material coating, a negative electrode sheet, and a lithium-ion battery containing the binder. The only difference from Embodiment 1 is that in step (2), the mass ratio of artificial graphite, silicon carbon material, conductive agent SP, and the dynamic crosslinking binder solution obtained in step (1) in the negative electrode sheet is 80:11:3:6. All other aspects are the same as in Embodiment 1.

[0094] Example 7 This embodiment provides a lithium-ion battery binder for inhibiting silicon expansion, as well as a negative electrode active material coating, a negative electrode sheet, and a lithium-ion battery containing the binder; the only difference from Embodiment 1 is that the preparation of the lithium-ion battery binder for inhibiting silicon expansion in step (1) is as follows: 0.7 g of polyacrylic acid (PAA, Mw=450,000) and 0.3 g of polyvinyl alcohol (PVA, degree of alcoholysis 99%, Mw=100,000) were dissolved together in 100 mL of deionized water to form a mixed polymer solution; then 0.6 g of dithiodipropionic acid was added, and the mixture was reacted at 80 °C for 3 h; after cooling to room temperature, a dynamic crosslinking adhesive solution was obtained, which is the lithium-ion battery adhesive for inhibiting silicon expansion described in this embodiment.

[0095] Example 8 This embodiment provides a lithium-ion battery binder for inhibiting silicon expansion, as well as a negative electrode active material coating, a negative electrode sheet, and a lithium-ion battery containing the binder; the only difference from Embodiment 1 is that the preparation of the lithium-ion battery binder for inhibiting silicon expansion in step (1) is as follows: 1.0 g of polyacrylic acid (PAA, Mw=450,000) was dissolved in 100 mL of deionized water. Subsequently, 0.6 g of dithiodipropionic acid and 0.8 g of 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride (EDC·HCl) as a condensing agent were added sequentially. The mixture was stirred at 80 °C for 3 h. After the reaction was completed, it was cooled to room temperature to obtain a PAA-disulfide bonded adhesive. After the adhesive solution cooled to room temperature, 5 mL of 0.1 mol / L ferric chloride (FeCl3) aqueous solution was slowly added dropwise while stirring continuously. The mixture was stirred for another hour to obtain a uniform dark red colloid, which is the lithium-ion battery adhesive for inhibiting silicon expansion described in this example.

[0096] Example 9 This embodiment provides a lithium-ion battery binder for inhibiting silicon expansion, as well as a negative electrode active material coating, a negative electrode sheet, and a lithium-ion battery containing the binder; the only difference from Embodiment 1 is that the preparation of the lithium-ion battery binder for inhibiting silicon expansion in step (1) is as follows: 0.5 g of polyacrylic acid (PAA) and 0.5 g of polyacrylamide (PAM, Mw=5,000,000) were dissolved together in 100 mL of deionized water; then 0.6 g of dithiodipropionic acid was added, and the mixture was reacted at 80 °C for 3 h; after the reaction was completed, the mixture was cooled to room temperature, and 5 mL of a 0.1 mol / L zinc acetate (ZnAc2) aqueous solution was slowly added dropwise with stirring, and stirring was continued for 1 h to obtain a colloid, which is the lithium-ion battery binder for inhibiting silicon expansion described in this example.

[0097] Example 10 This embodiment provides a lithium-ion battery binder for inhibiting silicon expansion, as well as a negative electrode active material coating, a negative electrode sheet, and a lithium-ion battery containing the binder; the only difference from Embodiment 2 is that the preparation of the lithium-ion battery binder for inhibiting silicon expansion in step (1) is as follows: The same method as in Example 2 was used to react phenylboronic acid with PAA to form a borate ester crosslinking network. After the reaction was completed, the mixture was cooled to room temperature, and 5 mL of 0.15 mol / L aluminum nitrate (Al(NO3)3) aqueous solution was slowly added dropwise while stirring. Stirring was continued for 1 h to obtain a colloid, which is the lithium-ion battery binder for inhibiting silicon expansion described in this example.

[0098] Comparative Example 1 This comparative example provides a lithium-ion battery binder, as well as a negative electrode active material coating, a negative electrode sheet, and a lithium-ion battery containing the binder; the only difference from Example 1 is that the lithium-ion battery binder is a pure PAA aqueous solution (solid content of 1%), and all other aspects are the same as in Example 1.

[0099] Comparative Example 2 This comparative example provides a lithium-ion battery binder, as well as a negative electrode active material coating, a negative electrode sheet, and a lithium-ion battery containing the binder; the only difference from Example 1 is that in step (1), the amount of crosslinking agent added is 1.2 g of dithiodipropionic acid, and all other aspects are the same as in Example 1.

[0100] Comparative Example 3 This comparative example provides a lithium-ion battery binder, as well as a negative electrode active material coating, a negative electrode sheet, and a lithium-ion battery containing the binder. The only difference from Example 1 is that in step (2), the mass ratio of artificial graphite, silicon carbon material, conductive agent SP, and the dynamic crosslinking binder solution obtained in step (1) in the negative electrode sheet is 80:11:0.1:8.9. All other aspects are the same as in Example 1.

[0101] Comparative Example 4 This comparative example provides a lithium-ion battery binder, as well as a negative electrode active material coating, a negative electrode sheet, and a lithium-ion battery containing the binder; the only difference from Example 7 is that in step (1), dithiodipropionic acid crosslinking agent is not added, and only 0.7 g PAA and 0.3 g PVA are dissolved in 100 mL of deionized water, stirred and mixed evenly, without heating and crosslinking reaction; all other aspects are the same as in Example 7.

[0102] Comparative Example 5 This comparative example provides a lithium-ion battery binder, as well as a negative electrode active material coating, a negative electrode sheet, and a lithium-ion battery containing the binder; the only difference from Example 8 is that a crosslinking reaction of dithiodipropionic acid is carried out, 1.0 g of PAA is dissolved in 100 mL of deionized water, and then 5 mL of 0.1 mol / L FeCl3 solution is directly added and stirred to form a coordination crosslinked gel; everything else is the same as Example 8.

[0103] Comparative Example 6 This comparative example provides a lithium-ion battery binder, as well as a negative electrode active material coating, a negative electrode sheet, and a lithium-ion battery containing the binder; the only difference from Example 8 is that the amount of FeCl3 aqueous solution added is 20 mL (0.1 mol / L); all other aspects are the same as Example 8.

[0104] Test case Test method: (1) Electrode peel strength test method: Cut the homogenized and dried negative electrode sheet into sample strips 15.0 mm ± 0.1 mm wide and 100 mm long. Take a piece of high-strength double-sided tape and attach it to the rigid substrate. With the current collector (copper foil) side of the electrode sample strip facing down, firmly adhere it to the double-sided tape, ensuring there are no air bubbles between the electrode and the substrate. Apply even pressure using a small roller or your fingers to ensure a firm bond. Carefully pry the active material layer from the copper foil at one end of the sample strip using tweezers, about 10-15 mm. Securely fix the rigid substrate to the lower clamping platform of the material testing machine. Bend the peeled active material layer vertically upwards at 90° and clamp it with the upper clamp, ensuring sufficient clamping area to prevent slippage. The peeling angle is 90°, the upper clamp moves vertically upwards at a peeling speed of 50 mm / min, and the peeling length is at least 50 mm. Start the testing machine to perform the peel test; the software records the peeling force and displacement curves in real time. From the peel force-displacement curve, select a stable peel segment of at least 30 mm in the middle and calculate the average peel force (F, in N) of this stable segment. Calculate the peel strength using the following formula: Peel strength = F / 0.015.

[0105] (2) Cyclic performance testing method: Place the battery in a 25°C constant temperature chamber for 6 hours and test it according to the following steps: (2-1) First round of constant current and constant voltage charging: Charge at a constant current of 0.1 C to 4.2 V, then switch to constant voltage charging until the current drops to 0.01 C.

[0106] (2-2) Let it stand for 30 minutes after charging is complete.

[0107] (2-3) Perform constant current discharge, discharging at a rate of 0.1C to 2.5V.

[0108] (2-4) Cyclic charge-discharge process: Charge at a constant current rate of 1C to 4.2V. Let stand for 30 minutes again. Discharge at a constant current rate of 1C to 2.5V.

[0109] (2-5) Repeat the above charging and discharging process for a total of 200 cycles.

[0110] Statistical analysis of the battery discharge capacity Q1 and Q2 after 1 and 200 cycles. 200 Calculate the battery capacity decay rate: (Q1-Q 200 ) / Q1×100%.

[0111] (3) Electrode expansion rate test method: First, the cycled lithium-ion battery was constant-current discharged to 2.5 V to ensure it was in a safe state, reducing the risk of short circuits or thermal runaway during disassembly. The battery was carefully disassembled inside a glove box (protected by argon or other inert atmosphere), and the negative electrode of the cylindrical cell was removed. The electrode was peeled off using plastic tweezers, taking care not to damage the active material layer. Next, the removed negative electrode was cut to an appropriate size and immersed in anhydrous dimethyl carbonate (DMC) solution for 30 minutes to dissolve and remove residual electrolyte and possible byproducts. After removing the electrode, the surface was gently wiped with lint-free paper, and then the immersion-wiping process was repeated three times with fresh DMC solution to ensure no residual contaminants remained on the electrode surface. Subsequently, the electrode was rinsed with anhydrous ethanol and wiped again to further remove solvent and impurities. After cleaning, the electrode was placed in a glove box and left to stand for 48 hours to ensure it was completely dry, preventing interference from residual solvent in subsequent testing. Electrode expansion rate: Electrode thickness after cycling / Initial electrode thickness × 100%.

[0112] The specific test results are shown in Table 1 below: Table 1

[0113] As shown in Table 1, the introduction of a dynamic covalent crosslinking network in Example 1 and Comparative Example 1 demonstrates a significant advantage over linear polymers. Comparative Example 1 used linear polyacrylic acid (PAA) as a binder, whose molecular chains were bound together only by weak van der Waals forces and interchain entanglement. Under the enormous volumetric expansion stress of the silicon particles, these physical forces were rapidly disrupted, causing relative slippage of the molecular chains, leading to the collapse of the bonded network (peel strength only 15 N / m), pulverization of the electrode structure (expansion rate as high as 32.5%), loss of connection between the active material and the current collector, and a sharp decline in capacity (only 58.4% after 200 cycles). In contrast, Example 1 established dynamic covalent crosslinking points between PAA chains using dithiodipropionic acid, forming a three-dimensional network. This network not only effectively limits excessive polymer slippage and provides higher mechanical strength (peel strength 52 N / m), but its core lies in the "dynamic reversibility" of disulfide bonds: at stress concentration points during charge and discharge, disulfide bonds undergo reversible breakage and recombination, converting concentrated stress into chemical bond breaking energy and dissipating it, thus preventing permanent network damage. This allows the electrode structure to remain intact during long-term cycling (expansion rate 8.2%) and achieve stable electrochemical performance (capacity retention 86.5%).

[0114] Examples 1 and 7-9 demonstrate that introducing non-covalent dynamic bonds (hydrogen bonds, coordination bonds) into a dynamic covalent network can produce a synergistic effect of "1+1>2". Example 1 (disulfide bonds only) provides a stable framework, but the energy dissipation mechanism is relatively simple. Example 7 (disulfide bonds + hydrogen bonds) introduces polyvinyl alcohol (PVA) or polyacrylamide (PAM), bringing a large number of hydroxyl or amide groups and forming a dense hydrogen bond network. Hydrogen bonds have moderate strength and extremely fast formation and breakage rates. As primary energy dissipation units, they can break / reassemble rapidly under slight deformation, consuming a large amount of energy, thus protecting the disulfide bond network from frequent impacts. This manifests as a significant improvement in adhesive toughness and initial adhesion (peel strength increases from 52 N / m to 65-75 N / m). Example 8 (disulfide bonds + coordination bonds) introduces Fe... 3+ Metal ions form coordination bonds with carboxyl groups. Coordination bonds are stronger than hydrogen bonds, significantly increasing the network modulus, making the electrode denser, and better suppressing the initial expansion of silicon particles (expansion rate reduced from 8.2% to 7.0%). Simultaneously, coordination bonds also exhibit dynamism, undergoing bonding-dissociation under higher stress, further enriching the energy dissipation pathways. In particular, Example 9 (triple dynamic bond) represents the pinnacle of synergistic effects, integrating the framework stability of disulfide bonds, the rapid energy dissipation of hydrogen bonds, and the high modulus strengthening effect of coordination bonds. These three dynamic bonds function sequentially or synergistically under different stress levels, constructing a broadband, efficient energy dissipation system, thereby achieving the lowest electrode expansion (6.2%) and the best long-term cycle life (92.8% capacity retention after 200 cycles).

[0115] Examples 7-8 and Comparative Examples 4-5 demonstrate the necessity of a dynamic covalent network as a framework. The networks in Comparative Example 4 (hydrogen bonds only) and Comparative Example 5 (coordination bonds only) rely entirely on non-covalent interactions. While hydrogen-bonded networks may perform reasonably well in a dry state, electrolyte solvent molecules (such as carbonates) strongly compete for and disrupt these bonds, leading to severe swelling and a sharp drop in strength (expansion rate as high as 25.1%) in the battery operating environment. Although coordination-bonded networks exhibit high dry-state strength, they are often too rigid or lack dynamism. Under long-term, large-scale volume changes, stress cannot be effectively released, easily leading to crack formation and propagation, resulting in brittle fracture. The capacity retention rates after 200 cycles are only 65.0% and 75.8%, respectively. The success of Examples 7-8 lies in their use of a dynamic covalent network as a permanent framework, ensuring the network's basic integrity and insolubility. Hydrogen bonds and coordination bonds act as sacrificial connection points on the framework, responsible for high-frequency energy dissipation. This "rigid-flexible" design ensures that the adhesive has both a solid matrix and excellent toughness and self-adaptability, resulting in higher 200-week capacity retention (89.5% and 90.2%).

[0116] As can be seen from Example 8 and Comparative Example 6, controlling the amount of ions used is crucial when introducing metal coordination bonds, and there exists an optimal window. Example 8 used an appropriate amount of Fe. 3+ This allows for the formation of a moderate density of coordination crosslinking sites between PAA chains. These sites enhance network stiffness while maintaining good dynamics. Comparative Example 6, however, used an excessive amount of Fe. 3+ This leads to excessively dense coordination crosslinking sites. Overly dense crosslinking makes the polymer network rigid, making chain segment movement difficult and greatly reducing its dynamics. This rigid network cannot effectively buffer volume expansion through bond breaking and recombination. Instead, it is like a brittle piece of glass, which is prone to macroscopic cracks under stress, leading to performance deterioration (capacity retention rate drops from 90.2% to 70.5% after 200 weeks).

[0117] Examples 2 and 10 demonstrate that the concept of multiple dynamic bonds proposed in this invention has universality, rather than being limited to a specific type of dynamic covalent bond. Example 2 uses phenylboronic acid and PAA to form a borate ester bond as the dynamic covalent framework. Example 10 further introduces Al based on this framework. 3+ -Carboxyl coordination bonds. The results are similar to those of the disulfide-based system (Example 8), both exhibiting superior performance compared to the single dynamic covalent bond system (both peel strength and 200-week capacity retention are higher than in Example 2). This strongly demonstrates that regardless of whether the dynamic covalent bond is a disulfide bond, borate ester bond, or imine bond, introducing hydrogen bonds or metal coordination bonds to construct a multiple dynamic network can achieve synergistic enhancement.

[0118] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and not to limit them; although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A lithium-ion battery binder for inhibiting silicon expansion, characterized in that, include: The first polymer has the following structural formula I: Formula I Where R is selected from or R1 and R2 are each independently selected from hydrogen or substituted or unsubstituted C1~C6 straight-chain or branched alkyl groups, and R3 is selected from hydrogen, substituted or unsubstituted C1~C6 straight-chain or branched alkyl groups, or substituted or unsubstituted C6~C12 aryl groups; m is 1~1000 and n is 1~1000.

2. The lithium-ion battery binder for inhibiting silicon expansion according to claim 1, characterized in that, R1 and R2 are each independently selected from C1-C4 straight-chain or branched alkyl groups; Preferably, R3 is selected from phenyl.

3. The lithium-ion battery binder for inhibiting silicon expansion according to claim 1, characterized in that, The lithium-ion battery binder that inhibits silicon expansion also includes a second polymer; The second polymer includes a functional group for forming hydrogen bonds with the first polymer; the functional group for forming hydrogen bonds with the first polymer includes any one or a combination of at least two of hydroxyl, amide, amino or carboxyl groups. Preferably, the mass ratio of the first polymer to the second polymer is 1:(0.1~10); Preferably, the second polymer comprises polyvinyl alcohol and / or polyacrylamide; Preferably, the weight-average molecular weight of the polyvinyl alcohol is 80,000 to 120,000; Preferably, the polyacrylamide has a weight-average molecular weight of 4,000,000 to 6,000,000.

4. The lithium-ion battery binder for inhibiting silicon expansion according to claim 1, characterized in that, The lithium-ion battery binder for inhibiting silicon expansion further includes a third compound comprising metal ions for forming metal coordination bonds with the first polymer; wherein the metal ions include Fe. 3+ Al 3+ Zn 2+ or Ca 2+ Any one or at least two of them; Preferably, the third compound comprises any one or a combination of at least two of chloride, acetate, sulfate, nitrate, acetate or oxalate; Preferably, the molar ratio of the first polymer to the third compound is 1:(0.01~0.5).

5. A method for preparing a lithium-ion battery binder for inhibiting silicon expansion according to any one of claims 1 to 4, characterized in that, The preparation method includes: Polyacrylic acid and a compound with dynamic reversible covalent bonds undergo a condensation reaction in a solvent to obtain the lithium-ion battery binder that inhibits silicon expansion.

6. The method for preparing the lithium-ion battery binder for inhibiting silicon expansion according to claim 5, characterized in that, When the lithium-ion battery binder for inhibiting silicon expansion further includes a second polymer, the preparation method includes: Polyacrylic acid, a second polymer, and a compound with dynamic reversible covalent bonds undergo a condensation reaction in a solvent to obtain the lithium-ion battery binder that inhibits silicon expansion. Preferably, when the lithium-ion battery binder for inhibiting silicon expansion further includes a third compound, the preparation method includes: Polyacrylic acid and a compound with dynamic reversible covalent bonds undergo a condensation reaction in a solvent to obtain a reaction solution containing a first polymer; the reaction solution containing the first polymer then undergoes a coordination reaction with a third compound to obtain the lithium-ion battery binder that inhibits silicon expansion. Preferably, when the lithium-ion battery binder for inhibiting silicon expansion further comprises a second polymer and a third compound, the preparation method includes: Polyacrylic acid, a second polymer, and a compound with dynamic reversible covalent bonds undergo a condensation reaction in a solvent to obtain a polymer mixed reaction solution; the polymer mixed reaction solution then undergoes a coordination reaction with a third compound to obtain the lithium-ion battery binder that inhibits silicon expansion. Preferably, the temperature of the condensation reaction is 60~80℃, and the time of the condensation reaction is 3~4 h; Preferably, the coordination reaction is carried out at a temperature of 20-30°C for 0.5-2 hours.

7. A negative electrode sheet, characterized in that, The negative electrode sheet includes a current collector and a negative electrode active material coating disposed on at least one side of the current collector; wherein the negative electrode active material coating includes a lithium-ion battery binder for inhibiting silicon expansion as described in any one of claims 1 to 4.

8. The negative electrode sheet according to claim 7, characterized in that, The content of the lithium-ion battery binder that inhibits silicon expansion accounts for 0.5-8% of the total mass of the negative electrode active material coating; Preferably, the negative electrode active material coating further includes graphite, silicon-based active material, and conductive agent; Preferably, the mass ratio of the graphite, silicon-based active material, conductive agent and the lithium-ion battery binder that inhibits silicon expansion is (70~95):(5~30):(1~10):(0.5~8).

9. A lithium-ion battery, characterized in that, The lithium-ion battery includes the negative electrode sheet as described in claim 7 or 8; Preferably, after 300 charge-discharge cycles at 1C, the capacity retention rate of the lithium-ion battery is >85%; Preferably, after three charge-discharge cycles, the peel strength between the negative electrode active material coating and the current collector is ≥60 N / m. Preferably, after 200 1C charge-discharge cycles, the thickness expansion rate of the negative electrode sheet is ≤8%.

10. An electrical appliance, characterized in that, The electrical device includes the lithium-ion battery as described in claim 9.

Citation Information

Cited By

  • Preparation method of interface enhanced positive electrode for sulfide all-solid-state battery

    CN121687873A

  • A preparation method of an interface-enhanced positive electrode for a sulfide all-solid-state battery

    CN121687873B